Infectious and Non-Infectious Factors Associated with Infertility in Cross-Bred Dairy Cows in Mid Terai Region of Nepal - Gautam, Gokarna; Kathayat, Binod Bahadur; Acharya, Madhav Prasad; Devkota, Bhuminand (Journal of Agriculture and Forestry University, 2025)
Infertility refers to the decrease of normal fertility, and it can be associated with various infectious and non-infectious factors. Brucellosis and neosporosis are important infectious causes of infertility in cattle. This study evaluated the association of brucellosis, neosporosis and some non-infectious factors with infertility in cross-bred dairy cows in mid terai region of Nepal. A questionnaire survey was conducted in 100 households from three districts of mid terai region to collect information related to infertility. The cows that did not conceive at least until five month postpartum were considered infertile. Serum samples obtained from 162 infertile cows (Chitwan-62, Nawalparasi-50, Rupendehi-50) were examined using ELISA kits to detect antibodies against Neospora caninum and Brucella abortus.These infertile cows were clinically examined for anemic condition (using eye’s mucous membrane)and body condition score (BCS). Overall, 4 (2.5%) and 9 (5.6%) cows were serologically positive for brucellosis and neosporosis, respectively. There was no association of brucellosis with abortion. Abortion cases were significantly higher in neosporosis positive cases (33.3%) than in neosporosis negative cases (9.8%). There was no association of brucellosis, neosporosis, breed and parity with repeat breeding. However, repeat breeding was more prevalent in cows having good nutritional status indicating that there might be other unknown factors causing repeat breeding. Likewise, there was no association of brucellosis, neosporosis and breed with anestrus. However, primiparity, low BCS, anemia, no drenching history since last calving and season of calving (spring and summer) were associated with anestrus in cross-bred dairy cows in mid terai region of Nepal.